Differential myocardial fibrosis of the systemic right ventricle and subpulmonary left ventricle after atrial switch operation for complete transposition of the great arteries() - Cheung, Yiu-fai (Int J Cardiol Heart Vasc, 2020)
BACKGROUND: This study aimed to assess diffuse myocardial fibrosis of the systemic right ventricle and subpulmonary left ventricle in patients after Senning or Mustard operation for complete transposition of the great artery (TGA) using cardiac magnetic resonance (CMR) T1 mapping. METHODS: Thirty-one adult TGA patients after Senning (n = 24) or Mustard (n = 7) operation were studied at the age of 33.3 ± 4.0 years. Systemic right ventricular (RV) and subpulmonary left ventricular (LV) volumes, ejection fraction, and myocardial T1 values and extracellular volume fraction (ECV) were determined using CMR. RESULTS: The RV and LV ejection fractions were 47.0 ± 10.9% and 61.3 ± 7.4%, respectively. Compared to published normative values, patients had significantly greater RV and LV native T1 and ECV values (all p < 0.001). For each of the basal, mid, and apical segments, the LV native T1 and ECV values were significantly greater in the left than the right ventricle (all p < 0.05). There is a significant trend on progressive increase in ECV value from the basal towards the apical segments in both the right (p = 0.002) and the left (p < 0.001) ventricle. Modestly strong correlations were found between RV and LV native T1 (r = 0.60, p < 0.001) and ECV (r = 0.49, p = 0.005) values but not with ejection fractions of the respective ventricles. CONCLUSIONS: Differential myocardial fibrosis, with greater involvement of the subpulmonary left ventricle than the systemic right ventricle, is present in patients with TGA after atrial switch operation. Associations between the magnitude of RV and LV fibrosis suggests adverse ventricular-ventricular interaction at the cardiac extracellular matrix level.